Aspergillus in COVID-19 intensive care unit; what is lurking above your head?. Issue 6 (November 2022) - Dailly, Sue; Boatswain, Erin; Brooks, Julie; Campbell, Glen; Dallow, Katy; Dushianthan, Ahilanandan; Glover, Sarah; Griffiths, Melanie; Gupta, Sanjay; Austin, James; Chambers, Robert; Jeremiah, Sarah; et al.
Introduction: Through routine respiratory samples surveillance among COVID-19 patients in the intensive care, three patients with aspergillus were identified in a newly opened general intensive care unit during the second wave of the pandemic. Methodology: As no previous cases of aspergillus had occurred since the unit had opened. An urgent multidisciplinary outbreak meeting was held. The possible sources of aspergillus infection were explored. The multidisciplinary approach enabled stakeholders from different skills to discuss possible sources and management strategies. Environmental precipitants like air handling units were considered and the overall clinical practice was reviewed. Settle plates were placed around the unit to identify the source. Reports of recent water leaks were also investigated. Results: Growth of aspergillus on a settle plate was identified the potential source above a nurse's station. This was the site of a historic water leak from the ceiling above, that resolved promptly and was not investigated further. Subsequent investigation above the ceiling tiles found pooling of water and mould due to a slow water leak from a pipe. Conclusion: Water leaks in patient areas should be promptly notified to infection prevention. Detailed investigation to ascertain the actual cause of the leak and ensure any remedial work could be carried out swiftly. Outbreak meetings that include diverse people with various expertises (clinical and non-clinical) can enable prompt identification and resolution of contaminated areas to minimise risk to patients and staff. During challenging pandemic periods hospitals must not lose focus on other clusters and outbreaks occurring simultaneously.